Control: China Story Yearbook 2016 - Golley, Jane; Jaivin, Linda; Tomba, Luigi (ANU Press, 2017)
'More cosmopolitan, more lively, more global' is how the China Daily summed up the year 2016 in China. It was also a year of more control. The Chinese Communist Party laid down strict new rules of conduct for its members, continued to assert its dominance over everything from the Internet to the South China Sea and announced a new Five-Year Plan that Greenpeace called 'quite possibly the most important document in the world in setting the pace of acting on climate change'. The China Story Yearbook 2016: Control surveys the year in China's economy, population planning, law enforcement and reform, environment, Internet, medicine, religion, education, historiography, foreign affairs, and culture, as well as developments in Taiwan and Hong Kong.